An HPLC Procedure for the Quantification of Aloin in Latex and Gel from Aloe barbadensis Leaves - Sánchez-Machado, D.I. (2017)
Aloin is an anthraquinone-C-glycoside present in Aloe vera. This compound is extremely variable among different species and highly depends on the growing conditions of the plants. The quantification of aloin in different extraction preparations has been a frequent problem due to the high instability of the compound. The aim of the present study is to develop and validated an analytical method for aloin detection in fresh and dry samples of Aloe barbadensis gel and latex using high performance liquid chromatography coupled to a diode array detector (HPLC-DAD). Phosphate buffered saline (pH 3) was selected as the extraction solvent. The aloin was separated using a Zorbax Eclipse AAA column (4.6 × 150 mm) at 35°C, and water and acetonitrile were used as the mobile phase at a flow rate of 0.9 mL/min. The linearity was satisfactory with a correlation coefficient greater than 0.999. Under these conditions, the method precision (relative standard deviation) was 3.71% for FL, 4.41% for dry latex, 0.81% for fresh gel and 4.42% for dry gel samples. Aloe latex was determined to have a greater amount of aloin than aloe gel. The method validation was satisfactory and exhibited adequate linearity, repeatability and accuracy.